Microbial translocation of needle-free injection enhanced beef strip loins as compared with traditional needle injection - Sutterfield, Ashley (Kansas State University, 2009)
The objective was to determine the effects of needle-free injection (NF) compared with traditional needle injection (N) on microbial translocation of generic E. coli in beef strip loins. Longissimus muscles (LM) (n=5) from USDA Select carcasses were used in preliminary research to determine the optimal injection pressure required for NF injections. Seven treatments with sterile colored saline solution were administered: 1) 90 psi ; 2) 55 psi ; 3) 50 psi ; 4) 45 psi ; 5) 30 psi ; 6) 25 psi ; or 7) 20 psi . For the second portion of the experiment 15 LM were obtained and halved; the surfaces were inoculated with generic E. coli at a level of 106 CFU/cm2 (three replications of five loins). Matching halves were allocated to NF or N injection treatments with a phosphate, salt solution. Immediately after injection, two cores, 23 cm2 in area, were taken aseptically from each half. A 2-mm thick cross-sectional slice was removed from the inoculated surface of the core and labeled “surface”. Using sterile technique, the two cores from each half were sliced into cross-sectional strips at depths of 1, 3, and 5 cm. Corresponding depth measurements were combined in stomacher bags with 99 ml of peptone water and stomached. Serial dilutions were then plated. From the preliminary study, it was determined that 25 psi was the optimal pressure for NF injection based on dispersion, visual appraisal, and solution retention. Samples taken from the surface of N injected LM had lower (P < 0.05) microbial counts than NF-injected muscles (2.79 versus 3.23 log CFU/g, respectively). The 3 and 5 cm depth samples from N injection had the least (P < 0.05) microbial contamination (1.69 and 2.12 log CFU/g) compared to NF injections. Samples from 1 cm deep of N injected LM had lower (P < 0.05) (2.53 log CFU/g) microbial counts than the 1 cm samples of NF injected LM (3.04 log CFU/g). Traditional N injection resulted in approximately 0.5 log CFU/g less microbial contamination at all depths. N injection posed fewer microbial risks when compared with NF injection using these defined application settings.
Keywords: Beef; Needle-free injection; Needle injection; Escherichia coli; Microbiology; Agriculture, Food Science and Technology (0359); Agriculture, General (0473); Biology, Microbiology (0410)